A systematic review of research into coach perspectives and behaviours regarding doping and anti-doping. (March 2022) - Barnes, Luke T.; Patterson, Laurie B.; Backhouse, Susan H.
Abstract: Objectives: Doping threatens the integrity of sport and the health and wellbeing of athletes. Operating as both a risk and protective agent, coaches may influence athletes' (anti-)doping thoughts, feelings and behaviours. The objective of this study was to systematically review empirical coach anti-doping literature over a 20-year period between World Anti-Doping Agency (WADA) formation (1999) and the present day (2019) to help better understand coaches' perspectives and behaviours in relation to doping and anti-doping in sport. Design: A systematic review was conducted using PRISMA guidelines. Methods: Electronic searches of seven databases, twenty-four journals and citation pearl growing identified published studies between 1999 and 2019. Results: Thirty-eight studies were included in this review. Three higher order themes were identified (individual, behavioural and contextual factors), consisting of a total of five themes (self-reported behaviour, hypothetical behaviour, coach beliefs, knowledge, and psychosocial components). Findings documented a changing research landscape, which revealed a greater frequency of total publications and emergence of qualitative study designs in conjunction with the development and induction of the 2015 World Anti-Doping Code (WADC). Conclusion: Over the last 20 years the anti-doping literature addressing coaches has developed and diversified from narrowly focused quantitative studies of coaches' knowledge and beliefs, to broader considerations of behavioural and contextual factors through the use of qualitative and mixed/multi-method designs. Although the existing literature sheds some light on coaches' perspectives and behaviours relating to doping prevention, further high-quality studies investigating the wider context surrounding coach behaviours, underpinned by meta-theory, are needed to fully understand the complexity of doping in sport and guide future policy and practice. Highlights: Τhe current evidence base has a limited theoretical underpinning. Τhe majority of studies focused on individual coach beliefs and knowledge. Recent studies explored behavioural and contextual factors surrounding coach (anti-)doping perspectives and behaviours. Despite holding anti-doping attitudes coaches' report limited anti-doping behaviours. Meta-theory should inform future research, recognising the complexity of doping.